Implementation of Husband’s Financial Support for Family Harmony and Stability: Islamic Family Law Perspectives and Digital Era Challenges - Maryam Nuh; Sabilul Muhtadin (Al-Fikru: Jurnal Ilmiah, 2026)
This study aims to analyze the implementation of the husband’s provision (nafkah) as the foundation of family stability and harmony within the perspective of Islamic family law, while also examining the challenges that arise in the digital era. The research employs a descriptive qualitative approach, with data collected through open-ended online questionnaires distributed to nine married respondents who are active social media users during the period of December 2025 to February 2026. The data were analyzed through triangulation with the Qur’an, hadith, the Compilation of Islamic Law (KHI), and the Family Stress Model. The findings indicate that provision is an absolute obligation of the husband, encompassing the fulfillment of both material and emotional needs in accordance with his economic capacity and the social conditions of the community. Proportional fulfillment of provision contributes significantly to the wife’s psychological well-being and the resilience of the family. However, exposure to lifestyle content on social media has the potential to trigger social comparison, dissatisfaction, and psychological pressure that affect household harmony. To address these challenges, it is necessary to strengthen the values of qana’ah (contentment), financial transparency, digital literacy, and effective communication so that families remain harmonious and resilient amid the rapid development of digital technology.